A Cyclic Method for Solutions of a Class of Split Variational Inequality Problem in Banach Space - Bashir Ali; Aisha A. Adam; Yusuf Ibrahim (Abstract and Applied Analysis)
In this paper, a cyclic algorithm for approximating a class of split variational inequality problem is introduced and studied in some Banach spaces. A strong convergence theorem is proved. Some applications of the theorem are presented. The results presented here improve, unify, and generalize certain recent results in the literature.